PROSPEK BISNIS DAN PEMBERDAYAAN UMKM DALAM PERSPEKTIF EKONOMI ISLAM: STUDI KASUS PADA USAHA PERMEN JAHE FADHILAH - Firman Happy; Achmad Tubagus Surur; Hendri Hermawan Adinugraha (Tamwil, 2021)
This study aims to describe the development strategy through the variables of natural resources, human resources, marketing, capital and technology in small and medium enterprises in the Pekalongan industrial sector in Buaran District, Pekalongan Regency. This study uses a qualitative research method with a descriptive approach. This type of research is field research. The results showed that the UMKM Fadhilah Ginger Candy in Sapugarut Gang 14 Village has a contribution to trust which is very important for the welfare of the community and increases the income of the surrounding community so that it can meet their daily needs such as food, as well as other needs such as housing, family health and necessities. It can be seen from the results of the research that the informants have experienced an increase in empowerment in the welfare of the community.